Solid-state NMR and thermodynamic investigations on LiBH4LiNH2 system. (24th August 2016) - Wolczyk, Anna; Pinatel, Eugenio R.; Chierotti, Michele R.; Nervi, Carlo; Gobetto, Roberto; Baricco, Marcello
Abstract: In this paper, Li2 (BH4 )(NH2 ) and Li4 (BH4 )(NH2 )3 compounds were prepared through different synthesis approaches (ball milling, annealing treatment and liquid quenching) and characterized by X-ray diffraction and solid-state NMR. The thermal analysis of samples with various (LiBH4 )1−x (LiNH2 )x compositions (0 ≤ x ≤ 1) have been performed by High Pressure DSC. Lattice constants, chemical shifts and relative phase stability obtained by DFT turned out in good agreement with experimental data. On the basis of a combination of ab-initio calculations and experimental data, a thermodynamic assessment of the LiBH4 LiNH2 system has been obtained using the Calphad method. Li2 (BH4 )(NH2 ) has been identified as a metastable phase and a peritectic melting of Li4 (BH4 )(NH2 )3 compound has been established. Highlights: Single Li2 (NH2 )(BH4 ) phase obtained by quenching, whereas Li4 (NH2 )3 (BH4 ) easily obtained with all synthesis routes. HP_DSC experiments allowed following the formation of the compounds, providing experimental data for phase transformations. ssNMR experiments on quenched samples confirmed the presence of compounds, providing information on the nuclei environments. Ab-initio calculations gave good agreement between experimental and the optimized lattice parameters and chemical shifts. Li2 (BH4 )(NH2 ) is formed as a metastable phase and a peritectic melting for the Li4 (BH4 )(NH2 )3 phase has been established.